Dialogical possibilities perceived in the Matrix Revolutions (2003) and some openings on the notions of geographical concepts (Revista Espinhaço, 2015)
This paper intends to establish a dialogue between the interpretative possibilities of the movie Matrix Revolutions, and portions of his trilogy, with discussions about the geographical concepts, namely place, region, territory, landscape and space. Thesenotions are also assumed as interpretive possibilities, in spite of converging with some definitions will be displayed. A major contribution of the Matrix’s trilogy refers to look for a complex and not easily demarcation of geographical concepts, that demonstrate to define and redefine in constant dialogue between them are established. Therefore, it will prioritize what the movie might be in each reading from every space - time rereading, and their multiple significations, in lively dialogue with geography science.
Keywords: Matrix; movie’s analysis; geographics concepts; space interpretations